(untitled) (Tempo e Argumento, 2020)
Diana Raznovich’s feminist graphic humor is an instrument of intervention aimed to discuss the discrimination suffered by women, exposing structures that imprisoned them in the final years of the twentieth century, context of feminist struggles. Understood as war-humor that has as effect the laughter, the production of the argentinian cartoonist, one of the first admittedly feminist graphic humorists in Latin America, demonstrates the complexity and fluidity of humor produced with a gender perspective, a challenge to the limited approaches of Humor Cultural History, marked by a canon and male theoretical elaborations. Facing this theoretical and historical scenario, this article intends to develop a historical analyses of Diana Raznovich’s feminist graphic humor. Focusing on discussions about the role of women in humor production, on debate about the ideas of private/public in humor, on change potential of feminist humor and on impact of discourses on femininity in the production of laughter, I intend, from texts and cartoons published in Latin American newspapers in the 1990s, discuss about revolutionary political potential of Diana Raznovich’s feminist humor. Keywords: Diana Raznovich. Feminism. Graphic Humor. War-humor. Latin America.